High-compaction-density ferric sodium pyrophosphate positive electrode material and preparation method thereof
By preparing highly active amorphous FePO4·xH2O and sintering treatment, the problem of low compaction density of sodium iron pyrophosphate positive electrode material is solved, and a high energy density sodium ion battery is realized, and the application range of the material is expanded.
Patent Information
- Application Number
- CN202510121444.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-24
- Publication Date
- 2025-05-06
- Estimated Expiration
- 2045-01-24
AI Technical Summary
The compaction density of existing sodium ferric phosphate cathode materials is low, resulting in a low energy density of sodium ion batteries, limiting their application.
By preparing highly active amorphous FePO4·xH2O and mixing it with a phosphorus source, supplementary sodium source and carbon source to make a precursor. After sintering, grain fusion is achieved between the primary particles to form secondary particles with high density, thereby increasing the compaction density of the positive electrode material of sodium iron phosphate pyrophosphate.
The compaction density of the sodium iron phosphate pyrophosphate positive electrode material has been significantly improved, the energy density of sodium ion batteries has been improved, and the application scenarios of the materials have been expanded.
Smart Images

Figure CN119929768A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a high compaction density sodium iron pyrophosphate positive electrode material and a preparation method thereof. Background Art
[0002] With the development of new energy vehicles, electrochemical energy storage technology based on secondary batteries is also constantly improving. Traditional lithium-ion batteries are limited by the scarcity of lithium resources and cannot meet the growing demand for energy storage. As a homologous element of lithium, sodium has similar physical and chemical properties to lithium. In addition, sodium is widely available and inexpensive, making it possible for sodium-ion batteries to partially replace lithium-ion batteries in new energy vehicles and other energy storage fields.
[0003] As an important component of sodium-ion batteries, the positive electrode material of sodium-ion batteries restricts the overall performance of the battery. At present, the positive electrode materials of sodium-ion batteries mainly include four types: oxides, polyanions, Prussian blue, and organic positive electrode materials. Among them, sodium iron pyrophosphate in the polyanion positive electrode material has a unique dimer structure and exhibits excellent electrochemical properties, which has attracted widespread attention from researchers.
[0004] Currently, researchers have conducted a lot of research on sodium iron pyrophosphate positive electrode materials and proposed many research methods to modify them, including carbon coating, anion doping, cation doping, anion-cation composite doping, etc., to further improve their performance. However, these existing modification methods are difficult to increase the compaction density of sodium iron pyrophosphate powder, and the lower compaction density will lead to a low energy density of sodium ion batteries prepared based on sodium iron pyrophosphate positive electrode materials, which restricts the application of sodium iron pyrophosphate positive electrode materials. Summary of the invention
[0005] In view of the technical problems existing in the background technology, the present application provides a high compaction density sodium iron pyrophosphate positive electrode material and a preparation method thereof, aiming to solve the technical problem of low compaction density of the sodium iron pyrophosphate positive electrode material.
[0006] In a first aspect, the present application provides a method for preparing a high compaction density sodium iron pyrophosphate positive electrode material, comprising the following steps:
[0007] Preparation of amorphous FePO 4 ·xH 2 O, where 1≤x≤4;
[0008] Amorphous FePO 4 ·xH 2 O is mixed with a phosphorus source, a supplemental sodium source, a carbon source and a solvent to obtain a first slurry;
[0009] Dispersing and drying the first slurry to obtain a precursor;
[0010] The precursor is sintered to obtain a sodium iron pyrophosphate positive electrode material.
[0011] In the technical solution of the embodiment of the present application, a highly active amorphous FePO 4 ·xH 2 O, and a mixture of a phosphorus source, a supplementary sodium source and a carbon source is made into a precursor, and then, through a sintering treatment, the primary particles are fused to form secondary particles with higher density, so as to achieve the effect of improving the compaction density of the sodium iron pyrophosphate positive electrode material.
[0012] In some embodiments, amorphous FePO 4 ·xH 2 The D50 of O particles is 3-5 μm, and the specific surface area is 50-60 m 2 / g.
[0013] In this embodiment, the prepared amorphous FePO 4 ·xH 2 O particles are small, the specific surface area is large, and the reaction activity is high, which makes it easier to achieve grain fusion, so that the prepared sodium iron pyrophosphate positive electrode material has a higher compaction density.
[0014] In some embodiments, amorphous FePO 4 ·xH 2 The preparation method of O comprises the following steps:
[0015] Mixing a divalent iron salt, phosphoric acid, an oxidant and water to obtain a mixed solution;
[0016] A pH regulator is added to the mixed solution until the pH value of the mixed solution is 1.8-2.0, and FePO is obtained after filtering and washing. 4 ·xH 2 O precipitation;
[0017] FePO 4 ·xH 2 O precipitation was dried to obtain amorphous FePO 4 ·xH 2 O, where 1≤x≤4.
[0018] In this embodiment, the prepared amorphous FePO can be prepared by mixing a divalent iron salt, phosphoric acid, an oxidant and water, and adjusting the pH value of the mixed solution to a specific range. 4 ·xH 2 O particle size and specific surface area are regulated to obtain amorphous FePO with small particles and large specific surface area. 4 ·xH2 O.
[0019] In some embodiments, the molar ratio of the divalent iron salt, phosphoric acid, and the oxidant is 1:(0.9-1.1):(0.4-0.6); and / or the divalent iron salt includes at least one of ferrous sulfate, ferrous chloride, and ferrous nitrate; and / or the oxidant includes at least one of hydrogen peroxide, ozone, and sodium hypochlorite; and / or the pH adjuster includes at least one of ammonia water, sodium hydroxide, potassium hydroxide, sodium carbonate, and potassium carbonate.
[0020] In this embodiment, by regulating the type of raw materials and their molar ratio, it is beneficial to promote the reaction to proceed efficiently to synthesize the desired amorphous FePO 4 ·xH 2 O, and the raw materials selected in this embodiment are widely available and inexpensive, and are suitable for industrial-scale production.
[0021] In some embodiments, the sintering process includes: the first stage of heating, heating to 150-200°C, and keeping warm for 1.5-2.5 hours; the second stage of heating, heating to 350-400°C, and keeping warm for 3.5-4.5 hours; the third stage of heating, heating to 500-600°C, and keeping warm for 13-15 hours.
[0022] In this embodiment, by regulating the specific temperature and holding time at different stages of the sintering process, the reaction raw materials can first form primary particles during the sintering process, and then the primary particles are fused to form high-density secondary particles, thereby effectively improving the compaction density of the sodium iron pyrophosphate positive electrode material.
[0023] In some embodiments, the phosphorus source includes at least one of sodium dihydrogen phosphate, ammonium dihydrogen phosphate, disodium hydrogen phosphate, and diammonium hydrogen phosphate; and / or, the supplemental sodium source includes at least one of sodium bicarbonate, sodium carbonate, sodium oxalate, sodium acetate, and sodium hydroxide; and / or, the carbon source includes at least one of polyethylene glycol, glucose, sucrose, starch, graphene, and carbon nanotubes.
[0024] In this embodiment, the optional range of phosphorus source, supplementary sodium source and carbon source is relatively wide, and the raw materials selected within this range can be used with amorphous FePO 4 ·xH 2 O reacts fully during the sintering process, thereby preparing a sodium iron pyrophosphate cathode material with a high compaction density.
[0025] In some embodiments, amorphous FePO 4 ·xH 2The molar ratio of O to the iron, phosphorus and sodium provided by the phosphorus source, the supplementary sodium source and the carbon source is (2.9-3.0): (3.9-4.1): (3.8-4.2); and / or, amorphous FePO 4 ·xH 2 The molar ratio of the iron element contained in O to the carbon element contained in the carbon source is (2.9-3.0):(1.6-2.0).
[0026] In this embodiment, the amorphous FePO4 is determined according to the stoichiometric ratio of each element in the target product sodium ferric pyrophosphate. 4 ·xH 2 The ratio of O to the phosphorus source and the supplementary sodium source can generate the required sodium iron pyrophosphate through the reaction. At the same time, this embodiment limits the ratio of carbon elements provided by the carbon source, and can control the thickness of the coated carbon layer, thereby improving the electronic conductivity of the sodium iron pyrophosphate positive electrode material while avoiding the excessively thick carbon coating layer affecting the transmission efficiency of sodium ions.
[0027] In some embodiments, the drying method is spray drying; the inlet air temperature of the spray drying is 150-250°C, and the outlet air temperature is 85-95°C.
[0028] In this embodiment, by spray drying the first slurry and regulating the temperatures of the inlet and outlet air, the precursor can be fully dried and formed into powder with a smaller particle size, so as to fully react in the subsequent sintering process.
[0029] In the second aspect, the embodiment of the present application provides a high compaction density sodium iron pyrophosphate positive electrode material, which is prepared by the preparation method provided in the first aspect; the compaction density of the sodium iron pyrophosphate positive electrode material is 2.0-2.2 g / cm 3 .
[0030] In the technical solution of the embodiment of the present application, the sodium iron pyrophosphate positive electrode material has a high compaction density, and applying it to a sodium ion battery can effectively improve the energy density of the sodium ion battery.
[0031] In some embodiments, the molecular formula of the sodium iron pyrophosphate positive electrode material is Na 4 Fe 2.91 P 2 O 7 (PO 4 ) 2 @C.
[0032] In this embodiment, the sodium iron pyrophosphate positive electrode material includes a molecular formula of Na 4 Fe 2.91 P 2 O 7 (PO 4) 2 The sodium iron pyrophosphate and the carbon coating layer coated on its surface make the positive electrode material have higher electronic conductivity and sodium ion transmission efficiency.
[0033] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] In order to more clearly illustrate the technical solution of the present application, the following is a brief introduction to the drawings used in the present application. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0035] Figure 1 This is a schematic diagram of the process flow of the preparation method of the high compaction density sodium iron pyrophosphate positive electrode material in Example 1 of the present application;
[0036] Figure 2 The amorphous FePO prepared in Example 1 of the present application 4 ·xH 2 XRD pattern of O;
[0037] Figure 3 The anhydrous FePO prepared in Comparative Example 1 of this application 4 XRD pattern of crystals;
[0038] Figure 4 This is a cross-sectional SEM image of the sodium iron pyrophosphate positive electrode material prepared in Example 1 of the present application;
[0039] Figure 5 This is a cross-sectional SEM image of the sodium iron pyrophosphate positive electrode material prepared in Comparative Example 1 of the present application;
[0040] Figure 6 The charge and discharge curves of the button half-cell assembled from the sodium iron pyrophosphate positive electrode material prepared in Example 1 of the present application. DETAILED DESCRIPTION
[0041] The following embodiments of the technical solution of the present application are described in detail in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.
[0042] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.
[0043] In the description of the embodiments of the present application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.
[0044] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0045] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of the associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.
[0046] Sodium iron pyrophosphate is an important positive electrode material for sodium ion batteries, but the compaction density of the sodium iron pyrophosphate positive electrode material prepared by conventional methods is low, resulting in a low energy density of the sodium ion battery prepared based on this positive electrode material, thus restricting the application of the sodium iron pyrophosphate positive electrode material.
[0047] In order to solve the technical problem of low compaction density of sodium iron pyrophosphate positive electrode material, the present application provides a high compaction density sodium iron pyrophosphate positive electrode material and a preparation method thereof, by preparing a highly active amorphous FePO 4 ·xH 2 O, and make it into a precursor with a mixture of a phosphorus source, a supplementary sodium source and a carbon source, and then sinter it to fuse the primary particles generated by the reaction to form secondary particles with higher density, so that the prepared sodium iron pyrophosphate positive electrode material has a higher compaction density.
[0048] In a first aspect, the present application provides a method for preparing a high compaction density sodium iron pyrophosphate positive electrode material, comprising the following steps:
[0049] S1. Preparation of amorphous FePO 4 ·xH 2 O, where 1≤x≤4;
[0050] S2, amorphous FePO 4 ·xH 2 O is mixed with a phosphorus source, a supplemental sodium source, a carbon source and a solvent to obtain a first slurry;
[0051] S3, dispersing and drying the first slurry to obtain a precursor;
[0052] S4. Sintering the precursor to obtain sodium iron pyrophosphate positive electrode material.
[0053] In the prior art, when preparing sodium iron pyrophosphate positive electrode materials, FePO 4 Crystals are used as raw materials, and the present application embodiment prepares amorphous FePO with high activity 4 ·xH 2 O as a raw material, and mixed with a phosphorus source, a supplementary sodium source and a carbon source to make a precursor, which can achieve grain fusion between primary particles through sintering. 4 Compared with the method of forming secondary particles by simple stacking of primary particles in the crystal structure, the secondary particles formed by primary particles through grain fusion in the embodiment of the present application have a higher density, so that the prepared sodium iron pyrophosphate positive electrode material has a higher compaction density. 4 ·xH 2 O can be omitted in the preparation of FePO 4 The aging step and the dehydration step during crystallization effectively improve the preparation efficiency and reduce the time and energy consumption costs. In the present application, preferably, the first slurry is dispersed by grinding.
[0054] Furthermore, in some embodiments, amorphous FePO 4 ·xH 2 The D50 of O particles is 3-5 μm, and the specific surface area is 50-60 m 2 / g.
[0055] In this application, amorphous FePO with small particle size and large specific surface area is prepared. 4 ·xH 2O particles can make it have higher reactivity, and it is easier to achieve grain fusion between the primary particles during the sintering process, thereby forming secondary particles with high density to improve the compaction density of the sodium iron pyrophosphate positive electrode material.
[0056] Furthermore, in some embodiments, amorphous FePO 4 ·xH 2 The preparation method of O comprises the following steps:
[0057] S10, mixing the divalent iron salt, phosphoric acid, an oxidant and water to obtain a mixed solution;
[0058] S11, adding a pH regulator to the mixed solution until the pH value of the mixed solution is 1.8-2.0, and filtering and washing to obtain FePO 4 ·xH 2 O precipitation;
[0059] S12, FePO 4 ·xH 2 O precipitation was dried to obtain amorphous FePO 4 ·xH 2 O, where 1≤x≤4.
[0060] The drying method includes filter pressing and / or low-temperature drying, wherein the temperature of low-temperature drying is preferably 60-75°C to remove free water while avoiding excessively high temperatures that may cause FePO 4 ·xH 2 O crystallization.
[0061] In the present application, by mixing divalent iron salt, phosphoric acid, oxidant and water, and adjusting the pH value of the mixed solution to 1.8-2.0, under this pH condition, amorphous FePO with small particle size and large specific surface area can be generated. 4 ·xH 2 O, its D50 is 3-5 μm, and its specific surface area is 50-60 m 2 / g, and has high reactivity. The preparation method is simple and easy to implement, and is easy to produce on an industrial scale, and does not require long-term aging and crystal water removal steps, and has high preparation efficiency.
[0062] Further, in some embodiments, the molar ratio of the divalent iron salt, phosphoric acid, and the oxidant is 1:(0.9-1.1):(0.4-0.6); and / or the divalent iron salt includes at least one of ferrous sulfate, ferrous chloride, and ferrous nitrate; and / or the oxidant includes at least one of hydrogen peroxide, ozone, and sodium hypochlorite; and / or the pH adjuster includes at least one of ammonia water, sodium hydroxide, potassium hydroxide, sodium carbonate, and potassium carbonate.
[0063] In the present application, by adjusting the ratio of each raw material according to the stoichiometric ratio required for the reaction, each raw material can be fully reacted to generate highly active amorphous FePO 4 ·xH 2 O. At the same time, the preferred raw materials in the embodiments of the present application are widely available and inexpensive, and can be suitable for industrial-scale production. Specifically, the molar ratio of the divalent iron salt, phosphoric acid, and the oxidant can be 1:0.9:0.4, 1:1.1:0.4, 1:0.9:0.6, 1:1.1:0.6, or any value within the range of 1:(0.9-1.1):(0.4-0.6).
[0064] Furthermore, in some embodiments, the sintering process includes: the first stage of heating, heating to 150-200°C, and keeping warm for 1.5-2.5 hours; the second stage of heating, heating to 350-400°C, and keeping warm for 3.5-4.5 hours; the third stage of heating, heating to 500-600°C, and keeping warm for 13-15 hours.
[0065] In the present application, by adopting a three-stage sintering method, pre-sintering is first performed in a low temperature section of 150-200°C, then the temperature is raised to a medium temperature section of 350-400°C for sintering, and finally sintering for a long time in a high temperature section of 500-600°C, which can not only promote the reaction to proceed fully and avoid the generation of impurities, but also promote the mutual fusion of the primary particles generated by the reaction to form secondary particles with higher density, thereby preparing a sodium iron pyrophosphate positive electrode material with a high compaction density. In addition, during the sintering process, the heating rate of each stage is preferably 1-3°C / min to ensure that the reaction proceeds stably and form a sodium iron pyrophosphate positive electrode material with a uniform and dense structure.
[0066] Further, in some embodiments, the phosphorus source includes at least one of sodium dihydrogen phosphate, ammonium dihydrogen phosphate, disodium hydrogen phosphate, and diammonium hydrogen phosphate; and / or, the supplementary sodium source includes at least one of sodium bicarbonate, sodium carbonate, sodium oxalate, sodium acetate, and sodium hydroxide; and / or, the carbon source includes at least one of polyethylene glycol, glucose, sucrose, starch, graphene, and carbon nanotubes.
[0067] In the present application, the preferred phosphorus source, supplementary sodium source and carbon source are all capable of reacting with the prepared highly active amorphous FePO 4 ·xH 2 O fully reacts during the sintering process, and the raw material selection range is wide, which can be selected according to actual needs, and can meet the needs of industrial-scale production. Among them, when sodium dihydrogen phosphate and / or disodium hydrogen phosphate are selected as the phosphorus source, it can provide the sodium element while providing the phosphorus element, thereby improving the utilization rate of the raw materials and correspondingly reducing the amount of the supplementary sodium source.
[0068] Furthermore, in some embodiments, amorphous FePO 4 ·xH 2 The molar ratio of O to the iron, phosphorus and sodium provided in the phosphorus source and the supplementary sodium source is (2.9-3.0):(3.9-4.1):(3.8-4.2); and / or, amorphous FePO 4 ·xH 2 The molar ratio of the iron element contained in O to the carbon element contained in the carbon source is (2.9-3.0):(1.6-2.0).
[0069] In this application, amorphous FePO 4 ·xH 2 The molar ratio of O, phosphorus source and supplementary sodium source can be determined according to the stoichiometric ratio of each element in the target product sodium ferric pyrophosphate, so that each raw material can be reacted to generate the required sodium ferric pyrophosphate. The chemical formula of sodium ferric pyrophosphate can be Na 4 Fe 3 P 2 O 7 (PO 4 ) 2 Or Na 4 Fe 2.91 P 2 O 7 (PO 4 ) 2 , by adjusting the amorphous FePO 4 ·xH 2 The amount of O used to change the content of iron can regulate the chemical formula of the prepared sodium iron pyrophosphate. When the iron content is low, the sodium iron pyrophosphate can form a small amount of iron-deficient phase, thereby forming vacancies to increase the transmission rate of sodium ions. However, if the iron content is too low, it is easy to produce impurities, resulting in a decrease in the capacity of the sodium ion battery prepared based on the positive electrode material. Specifically, amorphous FePO 4 ·xH 2 The molar ratio of O to the iron, phosphorus and sodium provided in the phosphorus source and the supplementary sodium source can be 2.9:3.9:3.8, 3.0:3.9:3.8, 2.9:4.1:3.8, 2.9:3.9:4.2, 2.9:3.9:3.8 or any value in the range of (2.9-3.0):(3.9-4.1):(3.8-4.2). Amorphous FePO 4 ·xH 2 The molar ratio of the iron element contained in O to the carbon element contained in the carbon source can be 2.9:1.6, 2.9:2.0, 3.0:1.6, 3.0:2.0 or any value in the range of (2.9-3.0):(1.6-2.0).
[0070] In addition, the embodiment of the present application can carbon-coat the sodium iron pyrophosphate by introducing a carbon source to improve its electronic conductivity. By limiting the proportion of carbon elements provided by the carbon source, the thickness of the coated carbon layer can be regulated, thereby improving the electronic conductivity of the sodium iron pyrophosphate positive electrode material while avoiding the excessively thick carbon coating layer affecting the transmission efficiency of sodium ions.
[0071] Furthermore, in some embodiments, the drying method is spray drying; the inlet air temperature of the spray drying is 150-250°C, and the outlet air temperature is 85-95°C.
[0072] In the present application, by spray drying the first slurry and regulating the temperature of the inlet and outlet air, the precursor can be fully dried and formed into powder with a smaller particle size, which is more conducive to the subsequent sintering process.
[0073] In the second aspect, the embodiment of the present application provides a high compaction density sodium iron pyrophosphate positive electrode material, which is prepared by the preparation method provided in the first aspect; the compaction density of the sodium iron pyrophosphate positive electrode material is 2.0-2.2 g / cm 3 .
[0074] Among them, the sodium iron pyrophosphate positive electrode material has a higher compaction density. Applying it in sodium-ion batteries can effectively improve the energy density of sodium-ion batteries and effectively expand the application scenarios of the sodium iron pyrophosphate positive electrode material.
[0075] Further, in some embodiments, the molecular formula of the sodium iron pyrophosphate positive electrode material is Na 4 Fe 2.91 P 2 O 7 (PO 4 ) 2 @C.
[0076] In this application, Na 4 Fe 2.91 P 2 O 7 (PO 4 ) 2 The iron vacancies formed in the pyrophosphate cathode material are beneficial to improving the sodium ion transport efficiency. 4 Fe 2.91 P 2 O 7 (PO 4 ) 2 The carbon coating on the surface can effectively improve the electronic conductivity of the sodium iron pyrophosphate cathode material, making the molecular formula Na 4 Fe 2.91 P 2 O 7 (PO4 ) 2 @C's sodium iron pyrophosphate cathode material has good electrochemical performance.
[0077] Some specific embodiments are listed below. It should be noted that the embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used without specifying the manufacturer are all conventional products that can be obtained commercially.
[0078] 1. Preparation method
[0079] Example 1
[0080] This embodiment provides a method for preparing a high compaction density sodium iron pyrophosphate positive electrode material, and its process flow chart is as follows: Figure 1 As shown, the following steps are included:
[0081] S1. Weigh ferrous sulfate heptahydrate, phosphoric acid and hydrogen peroxide in a molar ratio of 1:1:0.5, add them to deionized water, and fully dissolve them to obtain a mixed solution. 2+ The concentration of FePO4 was 0.5 mol / L; ammonia water was added to the mixed solution to adjust the pH value to 1.9. After sufficient reaction, the precipitate was collected by filtration, washed three times and filtered to obtain FePO4 4 ·xH 2 O precipitation; FePO 4 ·xH 2 The O precipitate was placed in a forced air drying oven and kept at 70 °C for 24 h to obtain amorphous FePO 4 3.8H 2 O, its D50 is 4.15 μm and its specific surface area is 52.3 m 2 / g.
[0082] S2. Take 2.91 mol of amorphous FePO 4 ·xH 2 O, add it with 1 mol of sodium dihydrogen phosphate dihydrate, 3 mol of sodium bicarbonate and 0.3 mol of glucose monohydrate into 4 L of deionized water to obtain a first slurry; grind the first slurry in a sand mill for 3 hours to obtain an off-white slurry; dry the slurry through a pressure spray dryer, set the spray inlet temperature to 180° C. and the outlet temperature to 90° C., and obtain a light yellow precursor powder after drying.
[0083] S3. The precursor powder is placed in a box-type atmosphere furnace for sintering treatment, and the heating curve is set as follows: heating to 180°C at a heating rate of 2°C / min, and keeping warm for 2h; then heating to 380°C at a heating rate of 2°C / min, and keeping warm for 4h; finally heating to 550°C at a heating rate of 2°C / min, and keeping warm for 14h, and then naturally cooling to room temperature to obtain a high compaction density sodium iron pyrophosphate positive electrode material, whose molecular formula is Na 4 Fe 2.91 P 2 O 7 (PO 4 ) 2 @C.
[0084] Example 2
[0085] This embodiment provides a method for preparing a high compaction density sodium iron pyrophosphate positive electrode material. Compared with Embodiment 1, the only difference is that the amorphous FePO used in step S2 is 4 ·xH 2 The amount of O was changed to 3 mol, and the remaining steps were consistent with Example 1. The molecular formula of the high compaction density sodium iron pyrophosphate positive electrode material obtained was Na 4 Fe 3 P 2 O 7 (PO 4 ) 2 @C.
[0086] Example 3
[0087] This embodiment provides a method for preparing a high compaction density sodium iron pyrophosphate positive electrode material. Compared with Example 1, the only difference is that the temperature rise curve during the sintering treatment in step S3 is changed, and the remaining steps are consistent with Example 1 and are not repeated here.
[0088] In this embodiment, the heating curve is set as follows: heating to 150°C at a heating rate of 2°C / min, keeping warm for 1.5 hours; then heating to 350°C at a heating rate of 2°C / min, keeping warm for 3.5 hours; finally heating to 500°C at a heating rate of 2°C / min, keeping warm for 13 hours, and then naturally cooling to room temperature.
[0089] Example 4
[0090] This embodiment provides a method for preparing a high compaction density sodium iron pyrophosphate positive electrode material. Compared with Example 1, the only difference is that the temperature rise curve during the sintering treatment in step S3 is changed, and the remaining steps are consistent with Example 1 and are not repeated here.
[0091] In this embodiment, the heating curve is set as follows: heating to 200°C at a heating rate of 2°C / min, keeping warm for 2.5 hours; then heating to 400°C at a heating rate of 2°C / min, keeping warm for 4.5 hours; finally heating to 600°C at a heating rate of 2°C / min, keeping warm for 15 hours, and then naturally cooling to room temperature.
[0092] Example 5
[0093] This embodiment provides a method for preparing a high compaction density sodium iron pyrophosphate positive electrode material. Compared with Example 1, the only difference is that the temperature rise curve during the sintering treatment in step S3 is changed, and the remaining steps are consistent with Example 1 and are not repeated here.
[0094] In this embodiment, the heating curve is set as follows: heating to 180°C at a heating rate of 1°C / min, keeping warm for 2 hours; then heating to 380°C at a heating rate of 1°C / min, keeping warm for 4 hours; finally heating to 550°C at a heating rate of 1°C / min, keeping warm for 14 hours, and then naturally cooling to room temperature.
[0095] Comparative Example 1
[0096] This comparative example provides a method for preparing a sodium iron pyrophosphate positive electrode material. Compared with Example 1, the only difference is that the preparation method in step S1 is changed to prepare FePO 4 crystals, and the FePO 4 Crystalline FePO instead of amorphous FePO 4 ·xH 2 O, sodium iron pyrophosphate positive electrode material was prepared according to steps S2-S3 in Example 1.
[0097] In this comparative example, FePO 4 The steps for preparing the crystals include:
[0098] First, prepare amorphous FePO according to step S1 in Example 1. 4 ·xH 2 O, and then the obtained amorphous FePO 4 ·xH 2 O was sintered in a muffle furnace at a sintering temperature of 600 °C, a heating rate of 5 °C / min, and kept at 600 °C for 2 h before cooling naturally to obtain anhydrous FePO 4 .
[0099] Comparative Example 2
[0100] This comparative example provides a method for preparing a sodium iron pyrophosphate positive electrode material. Compared with Example 1, the only difference is that the temperature rise curve during the sintering treatment in step S3 is changed, and the remaining steps are consistent with Example 1 and are not repeated here.
[0101] In this embodiment, the temperature rise curve is set as follows: heating to 550° C. at a heating rate of 2° C. / min, keeping the temperature for 14 hours, and then naturally cooling to room temperature.
[0102] Comparative Example 3
[0103] This comparative example provides a method for preparing a sodium iron pyrophosphate positive electrode material. Compared with Example 1, the only difference is that iron powder with an average particle size of 4 μm is directly used instead of amorphous FePO 4 ·xH 2 O, sodium iron pyrophosphate positive electrode material was prepared according to steps S2-S3 in Example 1.
[0104] 2. Test Method
[0105] 1. XRD test
[0106] The amorphous FePO prepared in Example 1 was chromatographed using an X-ray diffractometer. 4 ·xH 2 O and the anhydrous FePO prepared in Comparative Example 1 4 The crystal was tested.
[0107] 2. SEM test
[0108] The sodium iron pyrophosphate positive electrode materials prepared in Example 1 and Comparative Example 1 were detected using a scanning electron microscope.
[0109] 3. Compaction density test
[0110] The compaction density of the sodium iron pyrophosphate positive electrode materials prepared in Examples 1 to 5 and Comparative Examples 1 to 3 was tested using a compaction density meter in accordance with GB / T 24533-2019.
[0111] 4. Electrochemical performance test
[0112] The sodium iron pyrophosphate positive electrode materials prepared in Examples 1 to 5 and Comparative Examples 1 to 3 were respectively mixed with conductive carbon powder and PVDF binder in a mass ratio of 90:5:5, and then coated on an aluminum foil sheet after homogenization. After drying at 100° C., the sheets were rolled with a double-roller machine, and then a pole sheet with a diameter of 14 mm was obtained by a punching machine. The button half-cell was assembled in the order of negative electrode shell, sodium sheet, electrolyte, diaphragm, electrolyte, pole sheet, gasket, spring sheet, and positive electrode shell, and the electrochemical performance was tested.
[0113] III. Analysis of test results of various embodiments and comparative examples
[0114] Figure 2 The amorphous FePO prepared in Example 1 4 ·xH 2The XRD pattern of O is given by Figure 2 It can be seen that the FePO prepared in Example 1 4 ·xH 2 O is amorphous. Figure 3 The anhydrous FePO prepared in Comparative Example 1 4 The XRD pattern of Figure 2 compared to, Figure 3 There are obvious crystal diffraction peaks in the sample, indicating that the sample prepared in Comparative Example 1 is anhydrous FePO 4 Crystal. Figure 4 , Figure 5 The cross-sectional SEM images of the sodium iron pyrophosphate positive electrode materials prepared in Example 1 and Comparative Example 1 are shown in FIG. Figure 4 and Figure 5 It can be seen that Example 1 significantly improves the density of the positive electrode material compared to Comparative Example 1. Figure 6 is the charge and discharge curve of the battery assembled with the sodium iron pyrophosphate positive electrode material prepared in Example 1, Figure 6 It can be seen that the battery has good charge and discharge performance.
[0115] Table 1 shows the compaction density of the sodium iron pyrophosphate positive electrode materials prepared in Examples 1-5 and Comparative Examples 1-3 and the electrical performance data of the batteries assembled from the corresponding positive electrode materials. The electrical performance data are measured at a voltage of 2-3.5V and a rate of 0.1C.
[0116] Table 1
[0117]
[0118] It can be seen from Table 1 that the various embodiments of the present application prepare amorphous FePO 4 ·xH 2 O is used as a reaction raw material, and the temperature rise curve during the sintering treatment is regulated, so that a sodium iron pyrophosphate positive electrode material with a high compaction density can be prepared, and the secondary battery prepared based on the positive electrode material also has good electrochemical performance.
[0119] Specifically, by comparing the data of Example 1 and Example 2, it can be seen that the molecular formula is Na 4 Fe 2.91 P 2 O 7 (PO 4 ) 2 @C's sodium iron pyrophosphate cathode material is better than Na 4 Fe 3 P 2 O 7 (PO 4 ) 2@C has a higher compaction density and can make the prepared secondary battery have a higher charge and discharge capacity. By comparing the data of Example 1, Examples 3-5 and Comparative Example 2, it can be seen that the heating curve during the sintering treatment will affect the compaction density of the prepared sodium iron pyrophosphate positive electrode material and the electrochemical performance of the corresponding secondary battery, that is, in Comparative Example 2, the temperature is directly raised to 550°C, and no insulation treatment is performed in the low temperature section for a certain period of time, resulting in a lower compaction density of the prepared positive electrode material, and the discharge capacity of the secondary battery prepared based on the positive electrode material is also relatively low. By comparing the data of Example 1 and Comparative Example 1 and Comparative Example 3, it can be seen that in Comparative Example 1, the anhydrous FePO 4 The compaction density of the positive electrode material prepared when the crystal is used as the iron source is the lowest. In Example 1, amorphous FePO 4 ·xH 2 O as an iron source, compared with anhydrous FePO 4 Crystals or iron powder as an iron source can not only significantly increase the compaction density of the sodium iron pyrophosphate positive electrode material, but also enable the prepared secondary battery to have a higher charge and discharge capacity.
[0120] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A method for preparing a high compaction density sodium iron pyrophosphate positive electrode material, characterized in that: The steps include: Preparation of amorphous FePO4·xH2O, wherein 1≤x≤4; The amorphous FePO4·xH2O is mixed with a phosphorus source, a supplementary sodium source, a carbon source and a solvent to obtain a first slurry; Dispersing and drying the first slurry to obtain a precursor; The precursor is sintered to obtain a sodium iron pyrophosphate positive electrode material.
2. The method for preparing a high compaction density sodium iron pyrophosphate positive electrode material according to claim 1, characterized in that: The amorphous FePO4·xH2O particles have a D50 of 3 to 5 μm and a specific surface area of 50 to 60 m 2 / g.
3. The method for preparing a high compaction density sodium iron pyrophosphate positive electrode material according to claim 1, characterized in that: The preparation method of amorphous FePO4·xH2O comprises the following steps: Mixing a divalent iron salt, phosphoric acid, an oxidant and water to obtain a mixed solution; Adding a pH regulator to the mixed solution until the pH value of the mixed solution is 1.8-2.0, and filtering and washing to obtain a FePO4·xH2O precipitate; The FePO4·xH2O precipitate is dried to obtain amorphous FePO4·xH2O, wherein 1≤x≤4.
4. The method for preparing a high compaction density sodium iron pyrophosphate positive electrode material according to claim 3, characterized in that: The molar ratio of the divalent iron salt, phosphoric acid and oxidant is 1:(0.9-1.1):(0.4-0.6); and / or, The divalent iron salt includes at least one of ferrous sulfate, ferrous chloride and ferrous nitrate; and / or, The oxidant comprises at least one of hydrogen peroxide, ozone and sodium hypochlorite; and / or, The pH adjuster includes at least one of ammonia water, sodium hydroxide, potassium hydroxide, sodium carbonate and potassium carbonate.
5. The method for preparing a high compaction density sodium iron pyrophosphate positive electrode material according to claim 1, characterized in that: The sintering process comprises: The first stage is heating, heating to 150-200℃, and the heat preservation time is 1.5-2.5h; The second stage is heating, heating to 350-400℃, and the holding time is 3.5-4.5h; The third stage is heating up to 500-600°C and the heat preservation time is 13-15h.
6. The method for preparing a high compaction density sodium iron pyrophosphate positive electrode material according to claim 1, characterized in that: The phosphorus source includes at least one of sodium dihydrogen phosphate, ammonium dihydrogen phosphate, disodium hydrogen phosphate, and diammonium hydrogen phosphate; and / or, The supplementary sodium source includes at least one of sodium bicarbonate, sodium carbonate, sodium oxalate, sodium acetate and sodium hydroxide; and / or, The carbon source includes at least one of polyethylene glycol, glucose, sucrose, starch, graphene and carbon nanotubes.
7. The method for preparing a high compaction density sodium iron pyrophosphate positive electrode material according to claim 1, characterized in that: The molar ratio of the amorphous FePO4·xH2O to the iron element, phosphorus element and sodium element provided in the phosphorus source and the supplementary sodium source is (2.9-3.0):(3.9-4.1):(3.8-4.2); and / or The molar ratio of the iron element contained in the amorphous FePO4·xH2O to the carbon element contained in the carbon source is (2.9-3.0):(1.6-2.0).
8. The method for preparing a high compaction density sodium iron pyrophosphate positive electrode material according to claim 1, characterized in that: The drying treatment method is spray drying; the inlet air temperature of the spray drying is 150-250°C, and the outlet air temperature is 85-95°C.
9. A high compaction density sodium iron pyrophosphate positive electrode material, characterized in that: Prepared by the preparation method described in any one of claims 1 to 8; the compaction density of the sodium iron pyrophosphate positive electrode material is 2.0 to 2.2 g / cm 3 .
10. The method for preparing a high compaction density sodium iron pyrophosphate positive electrode material according to claim 9, characterized in that: The molecular formula of the sodium iron pyrophosphate positive electrode material is Na4Fe 2.91 P2O7(PO4)2@C.
Citation Information
Patent Citations
Carbon-coated iron phosphate sodium glass-ceramic composite material and preparation method thereof and application of carbon-coated iron phosphate sodium glass-ceramic composite material as a positive electrode material for secondary battery
CN107221664A
Preparation method of polyanionic sodium ion battery positive electrode material
CN117585659A
Modified ferric sodium pyrophosphate positive electrode material and preparation method thereof, positive electrode plate and sodium ion battery
CN118588913A
Single crystal type sodium ion battery positive electrode material and preparation method thereof
CN118943336A
Method for preparing battery-grade iron phosphate from copper smelting slag
CN119018866A
Cited By
High-tap-density ferric sodium pyrophosphate positive electrode material as well as preparation method and application thereof
CN121134716A